Integrated analysis of circRNA, lncRNA, miRNA and mRNA to reveal the ceRNA regulatory network of postnatal skeletal muscle development in Ningxiang pig - Yu, Zonggang; Xu, Xueli; Ai, Nini; Wang, Kaiming; Zhang, Peiwen; Li, Xintong; LiuFu, Sui; Liu, Xiaolin; Jiang, Jun; Gu, Jingjing; Gao, Ning; Ma, Haiming (Frontiers in Cell and Developmental Biology, 2023)
Introduction: The development of skeletal muscle is regulated by regulatory factors of genes and non-coding RNAs (ncRNAs). Methods: The objective of this study was to understand the transformation of muscle fiber type in the longissimus dorsi muscle of male Ningxiang pigs at four different growth stages (30, 90, 150, and 210 days after birth, n = 3) by histological analysis and whole transcriptome sequencing. Additionally, the study investigated the expression patterns of various RNAs involved in muscle fiber transformation and constructed a regulatory network for competing endogenous RNA (ceRNA) that includes circular RNA (circRNA)/long non-coding RNA (lncRNA)-microRNA (miRNA)-messenger RNA (mRNA). Results: Histomorphology analysis showed that the diameter of muscle fiber reached its maximum at 150 days after birth. The slow muscle fiber transformation showed a pattern of initial decrease followed by an increase. 29,963 circRNAs, 2,683 lncRNAs, 986 miRNAs and 22,411 mRNAs with expression level ≥0 were identified by whole transcriptome sequencing. Furthermore, 642 differentially expressed circRNAs (DEc), 505 differentially expressed lncRNAs (DEl), 316 differentially expressed miRNAs (DEmi) and 6,090 differentially expressed mRNAs (DEm) were identified by differential expression analysis. Functions of differentially expressed mRNA were identified by gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG). GO enrichment analysis indicates that 40 known genes and 6 new genes are associated with skeletal muscle development. Additionally, KEGG analysis shows that these genes regulate skeletal muscle development via MAPK, FoxO, Hedgehog, PI3K-Akt, Notch, VEGF and other signaling pathways. Through protein-protein interaction (PPI) and transcription factor prediction (TFP), the action mode of skeletal muscle-related genes was explored. PPI analysis showed that there were stable interactions among 19 proteins, meanwhile, TFP analysis predicted 22 transcription factors such as HMG20B, MYF6, MYOD1 and MYOG, and 12 of the 19 interacting proteins were transcription factors. The regulatory network of ceRNA related to skeletal muscle development was constructed based on the correlation of various RNA expression levels and the targeted binding characteristics with miRNA. The regulatory network included 31 DEms, 59 miRNAs, 667 circRNAs and 224 lncRNAs. conclusion: Overall, the study revealed the role of ceRNA regulatory network in the transformation of skeletal muscle fiber types in Ningxiang pigs, which contributes to the understanding of ceRNA regulatory network in Ningxiang pigs during the skeletal muscle development period.